(3EOGQI GdYedjGJ GdeUQajI GdeMdjI hGdeUQajI (B/s - (3YHO Gddg, NGdO Cejfs; (3GdWQGO, GSeGYjd GHQGgje s ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2006)
(3GdJYQja HGdLgGR GdeUQaj(B- (3GdYedjGJ GdeUQajI GdeMdjI(B- (3GdYedjGJ GdeUQajI GdNGQLjI(B- (3GdJehjd GdOhdj(B.s
Keywords: (3GdEOGQIs; (3GdeUGQas